A Scientometric Analysis of Research in Science Teaching in Non-Formal Environments in National Journals of the Teaching Area (2008 – 2019) - Barros, Lucas Guimarães; Langhi, Rodolfo [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2023)
This article is an investigation carried out in 184 articles published between 2008 and 2019 in 32 national journals classified in A1 and A2 level of the CAPES Teaching area. The aims were to realize a scientometric analysis of the academic research about the teaching science in non-formal environment, in order to build an overview with the main characteristics and trends of the area. Using Scientometrics as a tool for mapping and organizing data, it was identified: (a) a discrete growth of research on the subject in recent years; (b) predominance of empirical research; (c) a small number of authors who publish regularly, in contrast to a significant percentage of researchers who have published it once; (d) predominance of articles and books and book chapters as main references that underlie research, and; (e) a nucleus composed of three journals that concentrate one third of the total number of selected articles, while the rest of the production is scattered in twenty-nine journals. These results mark to the growth that Science Teaching in non-formal spaces still experiences in the research, as it is consolidated as a thematic topic of events and as a line of research in graduate programs in the Science Teaching area.
UM ESTUDO CIENCIOMÉTRICO DA PESQUISA EM ENSINO DE CIÊNCIAS EM ESPAÇOS NÃO FORMAIS EM PERIÓDICOS NACIONAIS DA ÁREA DE ENSINO (2008 – 2019)
Keywords: Non-Formal Education; Scientometrics; State of the Art